Familial Case of Cherubism from South India: Differential Diagnosis and Report of 2 Cases - Varun Muthuraman; Soundarya Srinivasan (Case Reports in Dentistry)
Cherubism is a rare familial multilocular cystic lesion of the jaws. The condition clinically appears as a bilateral symmetric swelling of the cheeks in children and is the primary reason for referral. It is a rare lesion of the jaws that has a dominant pattern of inheritance. We report two cases of cherubism, that of a boy and his mother suggestive of a strong familial incidence. A variety of lesions of the jaw mimic this condition and hence the differential diagnosis has been emphasised.